2004
DOI: 10.1074/jbc.m402176200
|View full text |Cite
|
Sign up to set email alerts
|

Ras Activates the Epithelial Na+ Channel through Phosphoinositide 3-OH Kinase Signaling

Abstract: Aldosterone induces expression and activation of the GTP-dependent signaling switch K-Ras. This small monomeric G protein is both necessary and sufficient for activation of the epithelial Na ؉ channel (ENaC). The mechanism by which K-Ras enhances ENaC activity, however, is uncertain. We demonstrate here that K-Ras activates human ENaC reconstituted in Chinese hamster ovary cells in a GTP-dependent manner. K-Ras influences ENaC activity most likely by affecting open probability. Inhibition of phosphoinositide 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 39 publications
7
76
1
Order By: Relevance
“…8.). In these experiments, ␣-and ␤ENaC migrated as overlying ϳ85-kDa bands and ␥ENaC as an ϳ80-kDa band, which is similar to that observed previously (8,29). As summarized in Fig.…”
Section: Fig 7 Rhoa Increases Enac Levels In the Plasma Membranesupporting
confidence: 71%
See 3 more Smart Citations
“…8.). In these experiments, ␣-and ␤ENaC migrated as overlying ϳ85-kDa bands and ␥ENaC as an ϳ80-kDa band, which is similar to that observed previously (8,29). As summarized in Fig.…”
Section: Fig 7 Rhoa Increases Enac Levels In the Plasma Membranesupporting
confidence: 71%
“…In previous work, we showed that Ras GTPases activate ENaC in a GTP-dependent manner (8). However, we also observed activation of ENaC by endogenous GTPases other than Ras.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…20 Our previous studies showed that several small G proteins, including K-Ras, RhoA, and Rab11a, alter ENaC activity. [21][22][23][24][25][26] The activity of small G proteins is modulated by guanine nucleotide exchange factors (GEFs). p21-activated kinase (Pak)-interacting exchange factor ␤ (␤Pix) is a member of the DBL (diffuse B cell lymphoma) family of Rho-GEFs for Rac1 and Cdc42.…”
mentioning
confidence: 99%